Attitudes of Primary Health Care Professionals Regarding Intimate Partner Violence Against Women - Cigdem CERIT; Ahmet Onder PORSUK (Anadolu Hemşirelik ve Sağlık Bilimleri Dergisi, 2021)
Aim: One of the most important components of primary health care is services provided to women. The aim of this study is to reveal the attitudes of health staff working in primary health care towards women who have been subjected to violence. Methods: The research is a descriptive and cross-sectional study conducted in the province of Kırklareli in September 2020. The population of the study consists of 686 healthcare professionals working in primary health care in Kirklareli. In the study, Turkish version of Attitudes and Practice of Health Care Providers Regarding Intimate Partner Violence Survey Scale was used. Descriptive and analytical statistics were used in the analysis of the data. The data were analyzed at 95% confidence level and p values less than 0.05 were considered significant. Results: 286 healthcare professionals participated in the study (N=286). 98 of the respondents are physicians (34.3%) and 188 (65.7%) are non-physician healthcare personnel and their average age is 40.56±10.03. The mean scale score of the participants was calculated as 103±6.24. It was observed that there was a statistically significant difference between the staff in the sub-dimensions of the Scale's Preparedness, Abuse Inquiry and Practitioner Lack of Control. Conclusion: In our study, it was determined that primary health care workers had some difficulties in detecting intimate partner violence against women. Considering that primary health care is a whole, efforts are needed to include all nurses, midwives and other personnel working in these services more into the process.